2014
DOI: 10.1016/j.neuroimage.2014.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of autocorrelation on functional connectivity

Abstract: Although the impact of serial correlation (autocorrelation) in residuals of general linear models for fMRI time-series has been studied extensively, the effect of autocorrelation on functional connectivity studies has been largely neglected until recently. Some recent studies based on results from economics have questioned the conventional estimation of functional connectivity and argue that not correcting for autocorrelation in fMRI time-series results in “spurious” correlation coefficients. In this paper, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 52 publications
3
91
2
Order By: Relevance
“…Is ψ homogeneous across the brain?). 7) It is well known that serial correlation intrinsically exists in the residuals or unaccounted-for part of the time series model for FMRI data due to physiological (cardiac and respiratory) confounds and thermal fluctuations in the scaner, which may lead to biased ISC estimates when heterogeneity of serial correlation occurs across subjects or brain regions (Arbabshirani et al, 2014). Nevertheless, recent investigation indicates that the impact of biased estimations on statistical inferences is minimal or even negligible (Arbabshirani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Is ψ homogeneous across the brain?). 7) It is well known that serial correlation intrinsically exists in the residuals or unaccounted-for part of the time series model for FMRI data due to physiological (cardiac and respiratory) confounds and thermal fluctuations in the scaner, which may lead to biased ISC estimates when heterogeneity of serial correlation occurs across subjects or brain regions (Arbabshirani et al, 2014). Nevertheless, recent investigation indicates that the impact of biased estimations on statistical inferences is minimal or even negligible (Arbabshirani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Correcting for this autocorrelation prior to calculating correlation values has been tried, and although it did not significantly impact network results in healthy participants (Arbabshirani et al, 2014), it may impact quantitative comparison of connectivity metrics between cohorts with different inherent autocorrelation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Individual and spatial differences in neurovascular coupling have been described (Schippers et al, 2011), and autocorrelation effects have predominantly been treated as a source of noise in the functional imaging literature. However, a previous study evaluating the relationship between autocorrelation of fMRI time series and traditional functional connectivity found that correcting for autocorrelation had little effect on traditional functional connectivity (Arbabshirani et al, 2014). Our results suggest that at least a component of the autocorrelative structure of BOLD signal may be due to differences in neural activity and could be related to cognition.…”
Section: Discussionmentioning
confidence: 99%